Independent Commissions and Contentious Issues in Post-Good Friday Agreement Northern Ireland - Walsh, Dawn. author. aut Link
XV, 236 p.
Keywords: “This richly original account of the role of independent commissions in resolving some of the most difficult and controversial issues in the Northern Ireland Peace Process provides an important and timely analysis that greatly enhances our understanding of the role of such commissions. It highlights the way in which they facilitate ongoing involvement by the international community in the implementation of peace settlements and outlines the way in which they play a mediating role between fiercely opposed views. This much-needed study helps to set a new agenda for research on this important but neglected aspect of peace processes.” Niall O’Dochartaigh, National University of Ireland Galway, Republic of Ireland.